In Situ Stress For Underground Excavation Design In A Naturally Fractured Rock Mass - Andrew J. Hyett (International Conference on Ground Control in Mining, 1989)
The ISRM commission on testing methods has recently presented Suggested Methods for rock stress determination (Kim & Franklin, 1987). This proposes that even if the magnitude of in situ stress is not sufficient to cause significant ground problems, the optimum shape, orientation, and layout of underground structures can be significantly affected by it. In the design of underground excavations, the engineer often requires a knowledge of the average in situ stress tensor in the rock mass. However, attempts to measure a stress state applicable to design have proved frustrating, and a high degree of uncertainty is introduced by the variability in results. In the belief that deduced fluctuations are random in nature, many separate measurements are often made, so that a more reliable stress tensor average, and some indication of the associated variance (see Dyke et al., 1986) can be calculated. Unfortunately, this approach is limited by economic considerations and, as with any sampling procedure, it is imperative to understand the sources of measured variability, in order to design an optimum measurement programme. Cundall(1987) itemised the main causes of stress variability as a. Instrument and measurement errors, and b. Natural fluctuations of stress from point to point, induced by the action of a boundary stress on the internal rock structure. At least four categories exist: i. inhomogeneous rock, bedding, intrusions etc.; ii. differential contraction, creep, or changes in rock properties with time; iii. proximity to faults or discontinuities; iv. cycles of tectonic activity that cause movement on joints. The latter was successfully investigated using the distinct element programme UDEC. In this paper, the contribution of items (iii) and (iv) (i.e. the items related to discontinuities) to the total stress variability will be discussed, for the kind of rock mass shown in Figure 1. Although many authors have concluded that rock joints have an influence on the stress in their vicinity, a more analytical approach is required if the stress distribution associated with different jointed rock masses is to be (i) compared, and (ii) related to routinely measured joint parameters. If this can be achieved then, prior to any attempt to measure stress in a jointed rock mass, a consideration of joint geometry, joint deformability, and the geological kinematics of joints (e.g. the magnitude and direction of previous movements), can place valuable `common sense' constraints on the expected stress system for minimal extra cost.